Evaluation of the criteria for the interpretation of the oral glucose tolerance test in the National Mother-Child Teaching Hospital ‘‘San Bartolome’’ - Moya Salazar, J. J.; Pio Dávila, L. (UANL. Facultad de Medicina, 2015)
Diabetes mellitus (DM) is a metabolic disorder that causes chronic hyperglycemia with disturbances in the metabolism of carbohydrates, fats and proteins, and alterations in microcirculation. We evaluate the criteria for the interpretation of the oral glucose tolerance test (OGTT) in the Hospital Nacional Docente Madre-Ni˜no ‘‘San Bartolomé’’ in Lima, Peru, and determine the percentages of pre-diabetic patients, diabetics that should not be included in the test, and those with alterations in their glucose curve during the biochemical determinations. To this purpose, a non-experimental, prospective cross-sectional analytic study was performed in 1271 patients, included in the study to comply with the guidelines and recommendations of the ADA and the CLSI POCT12-A3 guide, which were processed in the Biochemical Autoanalyzer Biosystems A25. Data analysis was performed using SPSS version 20.0 statistical analyzer, and respecting ethical diabetics. The main results are 1.97% diabetic and 13.85% pre-diabetic. The LJ phenomenon occurred with 6.45% (alteration in glucose curve after oral load decreases plasma glucose concentration determination after 60 min and returns at relatively higher than the basal concentration levels at 180 min) and 5.19% were poorly studied, including a >110 mg/dl baseline (p = <0.05). We determined a high rate of pre-diabetic patients and a reduced rate of diabetes coincident with Qiao et al. We highlight the usefulness of the OGTT, which must be rigorously evaluated, and reaffirm the importance of the LJ phenomenon as it may interfere with the final results of unsolved events, and evidence the importance of interindividual biological variability.